Influence Of Organizational Culture, Leadership Style And Competence Of Teacher Performance State SMA In East Oku: Influence Of Organizational Culture, Leadership Style And Competence Of Teacher Performance State SMA In East Oku - Helisia Margahana (Institute of Computer Science (IOCS), 2020)
This study aims to determine the Effect of Organizational Culture, Leadership Style, and Competence on the Performance of Public High School Teachers in East OKU. The implementation of this research for 3 (three) months includes designing, implementing and reporting the results of research. The study was conducted at SMA Negeri Timur OKU. In this study the total population was 70 people consisting of 30 people as a trial sample and 40 people as a research sample. Sampling in this study using a census sampling technique that is taking the sample as a whole from the total population. Based on the results of data analysis obtained regression coefficients for the regression coefficient variables for Organizational Culture variables of 0.269 with a significance level of 5%, Leadership Style by 0.304 with a significance level of 5%, regression coefficients for the Competence variable by 0.422 with a significance level of 5%, while insertion constant value of 13,856. Furthermore, the coefficient of the variable obtained by Organizational Culture is 0.269 with a significance of 5%, the Leadership Style variable with Teacher Performance is 0.305 with a significance level of 5%, the correlation coefficient for the Competency variable is 0.423 with a significance level of 5%, while the correlation coefficient (R) of 0.626 or 62.6% which means it has a very strong relationship between the independent variable and the dependent variable, also obtained a coefficient of determination (R2) of 0.757 This value can be interpreted that the large percentage of the influence of the variables of Leadership Style, Organizational Culture and Competence together with Teacher Performance 75.70%. In other words, the effective contribution of Organizational Culture, Leadership Style, and competence to the Performance of Teachers of Public High Schools in East OKU is 75.70% while the remaining 24.30% is influenced by other variables not included in this study.The conclusion of this study is that senior high school leaders in East OKU are advised to continuously improve their Organizational Culture, Leadership Styles and Competencies so that with their self-awareness together they always strive to achieve the goals that have been set together.